Perceived risk and perceived technology influence online purchase intention towards apparel / Salbiah Ibrahim and Nurfadilah Rahmat - Ibrahim, Salbiah; Rahmat, Nurfadilah (Faculty of Business and Management, 2016)
Purpose – To determine which factors influence the customer while purchase apparel via online medium such ad Instagram, Website and others. Through this research, we will discuss the factors influence online shopping intention towards apparel. Objective – To determine the level of factors influence online shopping intention towards apparel. Next is to determine the relationship between perceived risk and perceived technology towards online purchase intention. Last is to identify the most impactful factor between perceived risk and perceived technology towards online purchase intention. Methodology – A closed-ended questionnaire survey is conducted with sample size of 64 respondents. SPSS is used to find the data reliability, frequencies of data, Pearson Correlation test and Regression Test in order to test all the hypothesis involved and to also answer all the objective present. Summary of the findings – The results shows significant relationship between perceived risk and online purchase intention